2017
DOI: 10.1016/j.apsusc.2017.02.171
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembling of calcium salt of the new DNA base 5-carboxylcytosine

Abstract: Supramolecular architectures involving DNA bases can have a strong impact in several fields such as nanomedicine and nanodevice manufacturing. To date, in addition to the four canonical nucleobases (adenine, thymine, guanine and cytosine), four other forms of cytosine modified at the 5 position have been identified in DNA. Among these four new cytosine derivatives, 5-carboxylcytosine has been recently discovered in mammalian stem cell DNA, and proposed as the final product of the oxidative epigenetic demethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 102 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…NMR‐based solution studies of f C‐modified DNA duplexes, and NMR and crystallographic studies of the free nucleoside have confirmed that this is the preferred conformation . Similarly, the carboxylate group of ca C also appears to form such an intramolecular hydrogen bond; crystal structures show that the carboxylate group of ca C is coplanar with the cytosine ring, and an NMR study suggests the intramolecular hydrogen bond may even be stronger than that of f C, presumably because the carboxyl group is negatively charged at physiological pH. Another potential consequence of the negative charge is that electrostatic repulsion between dicarboxylated CpG steps might lead to greater structural distortion, forcing the ca C bases further apart than the normal ≈7.5 Å (the distance between the exocyclic carboxylate carbon atoms).…”
Section: Dna Containing Epigenetic Modifications: What Features Do Bimentioning
confidence: 88%
“…NMR‐based solution studies of f C‐modified DNA duplexes, and NMR and crystallographic studies of the free nucleoside have confirmed that this is the preferred conformation . Similarly, the carboxylate group of ca C also appears to form such an intramolecular hydrogen bond; crystal structures show that the carboxylate group of ca C is coplanar with the cytosine ring, and an NMR study suggests the intramolecular hydrogen bond may even be stronger than that of f C, presumably because the carboxyl group is negatively charged at physiological pH. Another potential consequence of the negative charge is that electrostatic repulsion between dicarboxylated CpG steps might lead to greater structural distortion, forcing the ca C bases further apart than the normal ≈7.5 Å (the distance between the exocyclic carboxylate carbon atoms).…”
Section: Dna Containing Epigenetic Modifications: What Features Do Bimentioning
confidence: 88%
“…Moreover, others presented DFT and classical MD simulations on the detailed configuration of (caC) 2 -calcium salt deposited on the highly oriented pyrolytic graphite surface. 22 In summary, most of the previous theoretical studies were focusing on the relevant chemical reactions and interaction with either TET protein in the catalytic cycle or metal ion, while the theoretical study on the initial properties such as photophysical and photochemical properties of the new four bases have received surprisingly little attention. As the basic carrier for genetic information on DNA, the nucleobases displayed well-documented photostability under persistent irradiation with ultraviolet light which could potentially induce deleterious structural damage or photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Jin and co-workers studied the activation free energies for the HSO 3 – induced deamination mechanism for 5caC and 5fC under typical bisulfite conditions by the MP2//B3LYP method. Moreover, others presented DFT and classical MD simulations on the detailed configuration of (caC) 2 -calcium salt deposited on the highly oriented pyrolytic graphite surface . In summary, most of the previous theoretical studies were focusing on the relevant chemical reactions and interaction with either TET protein in the catalytic cycle or metal ion, while the theoretical study on the initial properties such as photophysical and photochemical properties of the new four bases have received surprisingly little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Irrera et al. 40 fabricated a nanocomposite of self-assembled micrometrical fibers of PANI doped with ND. Energy dispersive X-ray (EDX) and Raman analysis revealed the self-assembled and ND doped nano-fibrils.…”
Section: Conducting Polymer/nanodiamond Nanocompositesmentioning
confidence: 99%